Autoimmune diseases in Turner syndrome: an overview - De Sanctis, Vincenzo; Khater, Doaa (Acta Biomedica Atenei Parmensis, 2019)
Turner syndrome (TS) results from a sex-chromosomal anomaly characterized by presence of one normal X chromosome and the loss of the second X-chromosome in phenotypic females. Autoimmunity has been recognized as one of the more prominent characteristics of TS. The risk of autoimmune diseases in patients with TS is approximately twice as high as in the general female population. The spectrum includes, Hashimoto’s thyroiditis, coeliac disease (CD), type 1 diabetes (T1DM), alopecia areata, inﬂammatory bowel disease, juvenile rheumatoid arthritis and some cutaneous disorders as vitiligo and Halo nevus. This review will address the autoimmune disorders associated with TS, their pathophysiologic mechanisms and clinical characteristics.